PENGARUH SPI, MORALITAS INDIVIDU DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECURANGAN AKUNTANSI (FRAUD) - Ni Komang Nita Pebriyani; Ni Komang Sumadi; Putu Cita Ayu (UNHI Press, 2022)
The purpose of this study is to find out influence of internal control systems, individual morality and compliance with accounting rules against accounting fraud. The location of this study was conducted at the Gianyar Sub-District All-Business Cooperative with a population in this study of 163 employees with the number of All-Business Cooperatives in Gianyar Subdistrict is 18 KSU. So that the number of samples in this study is determined by purposive sampling method according to the criteria, the number of samples was found as many as 107 respondents. The results of the test in this study found that 1) internal control systems have a negative and significant effect on accounting fraud (fraud). 2) individual morality has no significant effect on accounting fraud (fraud). 3) Variable compliance of accounting rules has a negative and significant effect on accounting fraud (fraud). The advice given is to check routinely finance in the cooperative and conduct meetings or discussions every month to check whether there are problems in the cooperative so that this can reduce acts of accounting fraud (fraud).